Incorporating trifunctional 1, 6-heptadiyne moiety into polyacetylene ionomer for improving its physical and conductive properties. Issue 19 (28th April 2020) - Li, Hongfei; Zhang, Hengchen; Liao, Xiaojuan; Sun, Ruyi; Xie, Meiran
Abstract : A trifunctional diyne comonomer can regulate the structure and optimize the physical state of polyacetylene ionomers, which exhibit a high ionic conductivity of 2.6 × 10 −5 –1.0 × 10 −3 S cm −1 at 30 °C. Abstract : Metathesis cyclopolymerization of a branched 1, 2, 3-triazolium-substituted 1, 6-heptadiyne ionic monomer and a tris(4- N, N -dipropargylaniline)amine trifunctional comonomer was conducted to afford a polyacetylene-based copolymer with a branched structure and flexible solid state when using an appropriate amount of comonomer, which performed better than the viscous semi-solid ionic homopolymer in forming a film. The branched copolymer exhibited a high intrinsic ionic conductivity of 2.6 × 10 −5 S cm −1 at 30 °C, which could reach 9.0 × 10 −5 S cm −1 and 1.0 × 10 −3 S cm −1 after doping with LiTFSI and a mixed dopant of ionic liquid/LiTFSI, respectively. Furthermore, the polyelectrolyte composite of LiTFSI-doped copolymer displayed good electrochemical stability with a high decomposition voltage of 5.2 V and ionic transference number of 0.39 versus Li/Li +, indicating that the flexible and stretchable copolymer has potential applications in electronic devices.